Associations of total nut and peanut intakes with all-cause and cause-specific mortality in a Japanese community: the Takayama study. Issue 9 (14th May 2022) - Yamakawa, Michiyo; Wada, Keiko; Koda, Sachi; Uji, Takahiro; Nakashima, Yuma; Onuma, Sakiko; Oba, Shino; Nagata, Chisato
Abstract: Numerous epidemiological studies have suggested that nut intake is associated with a reduced risk of mortality. Although diets and lifestyles differ by regions or races/ethnicities, few studies have investigated the associations among non-white, non-Western populations. We evaluated the associations of total nut and peanut intakes with all-cause and cause-specific mortality in a population-based prospective cohort in Japan. Participants (age: ≥35 years at baseline in 1992; n 31 552) were followed up until death or the end of follow-up in 2008. Those with cancer, CHD or stroke at baseline were excluded. Dietary intake was assessed only at baseline by using a validated FFQ. In total, 2901 men died during 183 299 person-years and 2438 women died during 227 054 person-years. The mean intakes of total nuts were 1·8 and 1·4 g/d in men and women, respectively. Although peanut intake accounted for approximately 80 % of the total nut intake, total nut and peanut intakes were inversely associated with all-cause mortality in men after adjusting for all potential confounders. For example, compared with the lowest quartile category, the adjusted hazard ratio (95 % CI) of total nut intake for all-cause mortality in men of the highest quartile category was 0·85 (95 % CI 0·75, 0·96) ( P for trend = 0·034). Peanut intake was inversely associated with digestive disease mortality in men and CVD mortality in women. Total nut and peanut intakes, even in low amounts, were associated with a reduced risk of mortality particularly in men.